2012
DOI: 10.1017/jfm.2012.207
|View full text |Cite
|
Sign up to set email alerts
|

Boundary layer structure in turbulent Rayleigh–Bénard convection

Abstract: The structure of the boundary layers in turbulent Rayleigh-Bénard convection is studied by means of three-dimensional direct numerical simulations. We consider convection in a cylindrical cell at an aspect ratio one for Rayleigh numbers of Ra = 3×10 9 and 3×10 10 at fixed Prandtl number P r = 0.7. Similar to the experimental results in the same setup and for the same Prandtl number, the structure of the laminar boundary layers of the velocity and temperature fields is found to deviate from the prediction of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
89
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(99 citation statements)
references
References 39 publications
8
89
2
Order By: Relevance
“…More recently, these authors further shown, again using numerical data, that the method works also in other positions in the horizontal plate other than the central axis (Zhou et al 2011) and in three-dimension (3D) cylindrical cell for moderate values of Ra (Stevens et al 2012). However, Scheel, Kim & White (2012) and Shi, Emran & Schumacher (2012), both using numerical approaches, have found that dynamic scaling works less well in the 3D cylindrical geometry than in the quasi-2D case. However, the method has not been tested experimentally so far in a 3D system.…”
Section: Boundary Layer Measurements In Turbulent Thermal Convectionmentioning
confidence: 97%
“…More recently, these authors further shown, again using numerical data, that the method works also in other positions in the horizontal plate other than the central axis (Zhou et al 2011) and in three-dimension (3D) cylindrical cell for moderate values of Ra (Stevens et al 2012). However, Scheel, Kim & White (2012) and Shi, Emran & Schumacher (2012), both using numerical approaches, have found that dynamic scaling works less well in the 3D cylindrical geometry than in the quasi-2D case. However, the method has not been tested experimentally so far in a 3D system.…”
Section: Boundary Layer Measurements In Turbulent Thermal Convectionmentioning
confidence: 97%
“…Currently, DNS for cylindrical cells with Γ = 1/2 can reach Ra = 2× 10 12 [79]. Since the numerical effort grows with Γ 2 when larger aspect ratio cells are considered, recent DNS at Γ = 1 achieved Ra = 3 × 10 10 only, but requiring almost the same number of grid points [80] as the former case for Γ = 1/2.…”
mentioning
confidence: 99%
“…addition, the horizontal flow is generated by the vertical hot/cold current that bends at the plates and bends again after having swept them; this phenomenon is accompanied by a streamwise pressure gradient that, in fact, is found in the numerical simulations by Shi et al (2012). In view of how different the conditions of the Rayleigh-Bénard flow are with respect to the Blasius boundary layer it is surprising how much the boundary layer profiles resemble each other.…”
Section: Overviewmentioning
confidence: 95%
“…The thickness of the viscous boundary layer δ v can be smaller than δ T for Pr < 1 and vice versa for Pr > 1. Assuming the correlation Nu 0.08Ra 0.32 it is trivial to estimate that for Pr = O(1) at Ra = 10 8 one obtains δ T ≈ δ v h/60 and at Ra = 10 12 the result is δ T ≈ δ v h/1100; the analysis of the boundary layer structure, therefore, requires large experimental setups (du Puits et al 2007) or high-resolution particle image velocimetry (Sun et al 2008) or high-fidelity direct numerical simulations (Shi, Emran & Schumacher 2012;Stevens et al 2012) for the highest Rayleigh numbers.…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation